The baseline levels of receptors and cytokines in phorbol 12-myristate 13-acetate-induced THP-1 monocyte to macrophage cells - Sri Wulandari; Tri Agusti Sholikah; Sinu Andhi Jusup (Universitas Nahdlatul Ulama Surabaya, 2026)
Monocyte-derived macrophages regulate various aspects of inflammation. Phorbol 12-myristate 13-acetate (PMA)-induced THP-1 monocytes are widely used as monocyte-derived macrophage models suitable for studying the pathophysiology of inflammation and developing therapies. However, there is insufficient data concerning the baseline expression of pro-inflammatory receptors and the associated cytokine levels in THP-1-derived macrophage-like cells compared with their monocyte precursors. In this study, PMA-treated THP-1 cells were employed as models for monocyte-derived macrophage-like cells (M0). The mRNA levels of Toll-like receptors (TLR)4, receptor for advanced glycation end-product (RAGE), and TLR7 in THP-1 cells, both with and without PMA treatment, were evaluated using quantitative real-time polymerase chain reaction (RT-qPCR). ELISA was performed to quantify IL-6, TNF-α, and IL-18 levels in the THP-1 culture supernatant. The mRNA expression of TLR4, RAGE, and TLR7 was increased twofold in PMA-induced THP-1-derived macrophage-like cells compared to monocytes. IL-6 (p = 0.0277) and TNF-α (p = 0.0105) levels were significantly elevated in the culture supernatants of THP-1-derived macrophages. However, IL-18 levels did not show a significant increase. The upregulation of TLR4, RAGE, and TLR7 transcription was accompanied by elevated secretion of IL-6 and TNF-α during PMA-induced differentiation of THP-1-derived macrophage-like cells (M0), highlighting the polarization state and the specific role of macrophages in producing pro-inflammatory cytokines. This study provides baseline data on pro-inflammatory receptor expression and cytokine production in the THP-1-derived macrophage-like cells model for inflammatory research.